Antibiotic Susceptibility Pattern of Bacterial Uropathogens causing Urinary Tract Infection in Patients attending Provincial Hospital, Janakpurdham, Nepal - Jha, Sanjeet Kumar; Thakur, Saroj Kumar; Yadav, Lalit Narayan; Kumari, Juni (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Distribution and susceptibility of UTI-causing pathogen varies according to place and time. Area specific monitoring studies, aimed to gain knowledge about the type of uropathogens and their susceptibility pattern, help clinicians choose the correct empirical treatment and reduce antibiotic resistance as well as treatment time and financial burden. MATERIALS AND METHODS: A hospital based cross-sectional study was carried out in provincial hospital, Madhesh province, Janakpurdham, Nepal from May 2021 to September 2021. Urine samples from 450 clinically suspected cases of UTI were collected and tested bacteriologically following standard procedure. Antibiotic susceptibility test was performed by the disk diffusion according to Clinical Laboratory Standard Institute (CLSI) guidelines. RESULTS: Of 450 urine samples,110(24.4%) showed significant bacterial growth. E. coli 57(51.82%) was the most common isolated followed by Pseudomonas aeruginosa18(16.36%). Most of the isolates were sensitive to Amikacin (AK), Amoxycillin Clavulanic Acid(AMC), Nitrofurantoin (NIT) whereas most of the gram positive and gram-negative isolates were resistant to Cefixime (CFM), Ampicillin (AMP), Cotrimoxazole (COT). CONCLUSIONS: This study showed that E. coli isolates were the predominant uropathogens and AMC is the most effective antibiotic. Most isolates were resistant to Cefixime (CFM), Ampicillin (AMP) and Cotrimoxazole (COT). The presence of highly resistive bacterial isolates, to some of the commonly prescribed drugs, limits the antibiotic prescription options. Drug resistance pattern is an ever-evolving process then isolates become resistant to commonly used drugs. So, frequent surveillance studies are conducted to update clinicians on effectiveness of empirical treatment for UTI.